Two new records for Costa Rican moss flora: Steereobryon subulirostrum and Pogonatum pensilvanicum (Polytrichaceae) - de Luna, Efraín; Ussher Miozzo, María Silvina; Cobos Acosta, Raquel (Instituto de Ecología, A.C., 2002)
As a result of field trips during the first “Tropical Bryology” course of the Red Latinoamericana de Botánica, we collected two species of Polytrichaceae that are new to the moss flora of Costa Rica and Central America: Steereobryon subulirostrum (Schimp. ex Besch.) G. L. Sm. and Pogonatum pensilvanicum (Hedw.) P. Beauv. The former taxon represents also a genus previously not known from Central America. In this connection we provide two identification keys, one for the genera of Polytrichaceae, and another for species of Pogonatum in Costa Rica.